Effect of single Ralgro® implant during the suckling period on reproductive performance of replacement heifers - Goehring, T.B.; Corah, L.R.; Simms, D.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and seven spring-born, crossbred heifers were used to determine the effect of a single Ralgro® implant on their reproductive performance. Three implant treatments were used: 1) Non-implanted controls, 2)36 mg Ralgro® at birth, or 3) 36 mg Ralgro® at 2 to 3 months of age. Heifers implanted at birth had significantly lower first service conception rates and overall pregnancy rules than non-implanted controls or those implanted at 2 to 3 months of age. Pelvic areas of yearling were increased by implanting at birth or 2 to 3 months of age. Age at puberty and the percentage of heifers cycling prior to the 22nd day of the 60-day breeding period were not influenced by treatment.
Keywords: Beef; Ralgro® implant; Reproductive performance; Replacement heifers